High-strength and high-transmittance high-alumina glass and preparation method thereof

The preparation method of high-aluminum glass is optimized through electric field-temperature gradient coupling enhancement technology, which solves the problems of high hardness and high light transmittance, and achieves the effects of high intensity and high transmittance. It is suitable for aerospace and high-precision optical instruments.

CN120398411AInactive Publication Date: 2025-08-01湖南兴怀新材料科技有限公司
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510905453.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-02
Publication Date
2025-08-01
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing high-aluminum glass preparation method cannot obtain glass with high hardness and high light transmittance at the same time. The traditional chemical strengthening method improves mechanical properties while reducing the light transmittance.

Method used

The electric field-temperature gradient coupling strengthening technology is used to treat high-aluminum glass under specific temperature and electric field conditions, including mixing, melting, forming, annealing and strengthening of ingredients, and using electric field to assist in accelerating ion migration to form a gradient compression stress layer, optimize SiO2 and Al2O3 content to control glass performance.

Benefits of technology

High-strength and high transmittance high alumina glass is obtained, which significantly improves the surface compression stress and stress layer depth. It is suitable for aerospace sighting systems and high-precision optical instruments, with reduced energy consumption and excellent thermal and chemical stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120398411A_ABST
    Figure CN120398411A_ABST
Patent Text Reader

Abstract

The invention discloses high-strength and high-transmittance high-alumina glass and a preparation method thereof, and belongs to the technical field of glass production, and the high-alumina glass comprises the following raw material components in mol%: 26 to 64.0% of SiO2, 10.0 to 15.0% of Al2O3, 10.0 to 15.0% of Na2O, 5.0 to 6.0% of K2O, 6.0 to 7.0% of MgO, 20 to 2.0% of ZrO, 0 to 0.5% of Fe2O3, 0 to 0.5% of Co2O3, 0 to 0.5% of CuO, and 0 to 0.5% of Cr2O3. Fe2O3 introduced in the raw materials is less than or equal to 0.01%; an electric field-temperature gradient coupling strengthening technology is adopted, and acceleration is assisted by an electric field: a 75V / cm direct-current electric field is applied to 30% Na + 70% K mixed salt at 410 DEG C; the method is obtained through a one-step strengthening method, mixed salt strengthening is used, and it is guaranteed that the surface stress is larger than or equal to 1000 MPa, and the stress layer depth DOL is larger than or equal to 50 micrometers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of glass production, and specifically relates to a high-aluminum glass and a preparation method thereof. Background Art

[0002] Due to its high strength, wear resistance and chemical stability, high-aluminum glass is widely used in cover glasses for electronic devices such as smartphones and tablets, as well as in the military, transportation and other fields. Traditional soda-lime-silica glass is difficult to meet the requirements of high-end devices due to its insufficient impact resistance (such as low passing rate in the ball-drop test). High-aluminum glass can significantly improve the surface compressive stress (CS) and the depth of the stress layer (DOL) through chemical strengthening, thereby improving the anti-drop and anti-scratch properties.

[0003] CN 117486485 A discloses a high-strength performance glass and its preparation method and application. The surface stress of the glass can reach more than 1000 MPa, but there is a problem of low light transmittance when the surface stress is increased, and it cannot meet the requirements of both high hardness and high light transmittance.

[0004] CN 113800786 A discloses a chemical strengthening method for medium-high aluminum silicate glass fibers. The strengthening method replaces ions with smaller radii on the surface of glass fibers with ions with larger radii to form a compressive stress layer on the surface of the glass fibers, so as to improve the mechanical properties of the glass fibers. This method can only improve the mechanical properties of the glass, but there is still a problem of reduced light transmittance while improving the mechanical properties.

[0005] The existing preparation methods of high-aluminum glass have the problem that it is impossible to obtain glass with both high hardness and high light transmittance. In view of this, the present invention provides a high-aluminum glass with high strength and high transmittance and a preparation method thereof. Summary of the Invention

[0006] In view of the above problems, the present invention provides a subject name to solve the problem that the existing preparation methods of high-aluminum glass cannot obtain glass with both high hardness and high light transmittance.

[0007] According to one aspect of the present invention, there is provided a high-aluminum glass with high strength and high transmittance. In mol%, its raw material components include 60.0 - 64.0% of SiO2, 10.0 - 15.0% of Al2O3, 10.0 - 15.0% of Na2O, 5.0 - 6.0% of K2O, 6.0 - 7.0% of MgO, 0 - 2.0% of ZrO2, 0 - 0.5% of Fe2O3, 0 - 0.5% of Co2O3, 0 - 0.5% of CuO, 0 - 0.5% of Cr2O3; in mol%, Fe2O3 cited in the raw materials ≤ 0.01%; The high-aluminum glass adopts the electric field-temperature gradient coupling strengthening technology during the preparation process, and is assisted by an electric field to accelerate: a DC electric field of 75 V / cm is applied in a 30% Na+70% K mixed salt at 410 °C, and the strengthening time is 3 h.

[0008] Since the skeleton component of the glass is mainly composed of SiO2, a reasonable range needs to be determined for its composition requirements. As a glass network former, when the content of SiO2 is too low, the chemical stability of the obtained glass will deteriorate; when the content of SiO2 is too high, the network connection of the glass will be reduced, thereby reducing the viscosity and melting temperature, and it is difficult to effectively temper the glass because its structure is stable and it is difficult to carry out ion migration, making it difficult to form the required surface pressure layer. Therefore, through a large number of studies, the content of SiO2 in the present invention is limited to 60-64% (in mol%). As an intermediate oxide of the glass, when the content of Al2O3 is too low, the glass is prone to crystallization; when the content of Al2O3 is too high, the viscosity of the glass melt is large and a higher melting temperature is required. Therefore, through a large number of studies, the content of Al2O3 in the present invention is limited to 10.0-15.0% (in mol%).

[0009] According to the second aspect of the present invention, a method for preparing a high-aluminum glass with high strength and high transmittance is provided. The preparation method includes at least the following steps: Step 1: Weigh the raw materials according to the above component ratios, load them into a mixer and mix evenly to obtain the evenly mixed raw materials; Step 2: Melting, place the raw materials evenly mixed in Step 1 in a melting furnace for melting to obtain the melted glass liquid; Step 3: Forming, form the melted glass liquid obtained in Step 2 in a press to obtain the formed glass; Step 4: Annealing, place the formed glass obtained in Step 3 in an annealing furnace for annealing to obtain the high-aluminum glass to be strengthened; Step 5: Strengthening, strengthen the high-aluminum glass to be strengthened obtained in Step 4 to obtain the high-aluminum glass with high strength and high transmittance; Step 6: Performance testing, perform performance testing on the high-aluminum glass with high strength and high transmittance obtained in Step 5.

[0010] Furthermore, the conditions for melting in Step 2 are as follows: The melting temperature is 1600-1650 °C; The melting time is 3-8 h.

[0011] Furthermore, the conditions for forming in Step 3 are as follows: The forming temperature is 880-950 °C; The forming time is 4 - 6 h.

[0012] Further, the annealing conditions in Step 4 are as follows: The annealing temperature is 610 - 645 °C; The annealing time is 2 - 8 h; The glass to be strengthened in Step 4 has a transmittance of 90 - 95% at 550 nm and a strain point of 560 - 595 °C.

[0013] Further, the mixed salt in Step 5 is selected from at least one of potassium nitrate, potassium carbonate, and potassium chloride; The concentration of the mixed salt is 0.1 - 4 mol / L; The strengthening conditions in Step 5 are as follows: The strengthening temperature is 400 - 450 °C; The strengthening time is 1 - 10 h.

[0014] Further, the surface stress of the high - strength and high - transmittance high - alumina glass in Step 5 is ≥1000 MPa, and the depth of the stress layer DOL ≥50 μm.

[0015] Compared with the prior art, the beneficial effects of the present invention are: (1) The softening point temperature of the high - strength and high - transmittance high - alumina glass obtained by the technical solution disclosed in the present invention is greater than 800 °C, significantly higher than that of conventional soda - lime glass; the melting point temperature ranges from 1600 °C to 1650 °C; through a precisely controlled strengthening process, under the conditions of a strengthening temperature range of 400 - 450 °C, a gradient heating and cooling system, and a total duration of not more than 5 hours, excellent mechanical properties can be obtained - the surface compressive stress (CS value) ≥1000 MPa, and the depth of the stress layer (DOL) ≥100 μm; this material has both excellent thermal stability and chemical stability, and is suitable for cutting - edge fields such as aerospace observation and aiming systems and high - precision optical instruments.

[0016] (2) The technical solution disclosed in the present invention designs a gradient Al 3+ distribution, that is, the surface Al 3+ concentration is 2 - 3% higher than that inside. Through the regulation of the ion migration barrier, a gradient compressive stress field is formed (900 MPa at the surface → 600 MPa at the core), avoiding brittle fracture caused by stress mutation.

[0017] (3) The technical solution disclosed in the present invention uses an electric - field - temperature gradient coupling strengthening technology. Through electric - field assistance to accelerate: applying a 50 - 80 V / cm DC electric field in a 410 °C mixed - salt molten salt to drive the directional migration of K + The ion - exchange efficiency is increased by 2.3 times (up to 4.5×10 -14m² / s), single strengthening time: it can achieve the effect of traditional three - time strengthening (24 hours) in 4 - 6 hours, with energy consumption reduced by 65%. Brief Description of the Drawings

[0018] Figure 1 It is the microscope scanning transmission image of the high - strength and high - transmittance high - alumina glass prepared after strengthening in Example 1 of the present invention; Figure 2 It is the physical image of the high - strength and high - transmittance high - alumina glass prepared after strengthening in Example 1 of the present invention. Detailed Embodiments

[0019] In order to enable those skilled in the art to better understand the technical solution, the present invention will be described in detail below in combination with embodiments. The description of this part is only exemplary and explanatory, and should not have any restrictive effect on the protection scope of the present invention.

[0020] The introduction amount of the raw material Fe2O3 is not higher than 0.01% (in mol%). It is found that under this preferred specific embodiment, the high - alumina glass provided by the present invention has better visible light transmittance.

[0021] This preferred embodiment adopts the electric - field - temperature - gradient coupling strengthening technology, and accelerates through electric - field assistance: applying a 75V / cm DC electric field in a 30% Na+70% K mixed salt at 410℃, and using a strengthening time of 3h, higher strength and stress layer depth can be obtained.

[0022] Example 1

[0023] This example discloses a high - strength and high - transmittance high - alumina glass, which includes the following steps: Step 1: Batching and mixing. Each raw material is proportioned according to the component ratio in Table 1, and the raw materials are loaded into a mixer and mixed evenly to obtain the evenly - mixed raw materials; Step 2: Melting. The evenly - mixed raw materials obtained in Step 1 are placed in a melting furnace and melted at 1640℃ for 6h to obtain the melted glass liquid; Step 3: Forming. The melted glass liquid obtained in Step 2 is formed in a press at 900℃ for 4h to obtain the formed glass; Step 4: Annealing. The formed glass obtained in Step 3 is placed in an annealing furnace and subjected to precision annealing treatment at 640℃ for 4h to obtain the high - alumina glass to be strengthened; Step 5: Strengthening. Place the high-aluminum glass to be strengthened obtained in Step 4, 20 ml of a KNO3 and NaNO3 solution with a concentration of 4 mol / L in a glass gradient polarization strengthening machine, apply a DC electric field of 75 V / cm at 410 °C for 3 h to obtain the strengthened high-aluminum glass (i.e., high-aluminum glass with high strength and high transmittance). The micrograph of the strengthened high-aluminum glass is as shown in Figure 1 shown, and the physical diagram is shown by Figure 2 ; Step 6: Performance testing. Perform performance testing on the strengthened high-aluminum glass obtained in Step 5. The performance test results are shown in Table 2.

[0024] In Examples 2 to 6 and Comparative Examples 1 to 2, except that the component ratios are different from those in Example 1, the introduction amount of the raw material component Fe2O3 used in the comparative examples is higher than 0.01% (in mol%) and is also different from that in the examples. The steps of batching and mixing, melting, forming, annealing, strengthening, etc. in Steps 1 to 6 are the same.

[0025] Table 1 shows the raw material composition ratios of Examples 1 to 6 and Comparative Examples 1 to 2

[0026]

[0027] It can be seen from the results of the above-selected examples and comparative examples that when the introduction amount of the raw material Fe2O3 is not higher than 0.01%, glass with higher transmittance can be obtained, and a reasonable content range of SiO2 will also affect the performance of the chemically strengthened glass. By adopting the selected preferred method of the present invention, while taking into account the transmittance, it can ensure that the glass has better strength at the same time.

[0028] It should be noted that in this article, the terms: including, containing and any other variants are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements not only includes those elements, but also includes other elements not expressly listed, or also includes elements inherent in such a process, method, article or device. Specific examples are used in this article to elaborate on the principle and implementation manner of the technical solution of the present invention. The description of the above examples is only used to help understand the method and its core idea of the present invention. The above description is only the preferred implementation manner of the present invention. It should be pointed out that due to the limited nature of written expression and objectively existing infinite specific structures, for those of ordinary skill in the art, without departing from the principle of the present invention, several improvements, refinements or changes can be made, or the above technical features can be combined in an appropriate manner; these improvements, refinements, changes or combinations, or directly applying the concept and technical solution of the present invention to other occasions without improvement, should all be regarded as the protection scope of the present invention.

Claims

1. A high-strength, high-transmittance high-aluminum glass, characterized in that: In mol%, its raw material components include 60.0 - 64.0% of SiO₂, 10.0 - 15.0% of Al₂O₃, 10.0 - 15.0% of Na₂O, 5.0 - 6.0% of K₂O, 6.0 - 7.0% of MgO, 0 - 2.0% of ZrO₂, 0 - 0.5% of Fe₂O₃, 0 - 0.5% of Co₂O₃, 0 - 0.5% of CuO, 0 - 0.5% of Cr₂O₃; In mol%, Fe₂O₃ cited in the raw materials ≤ 0.01%; During the preparation of the high-aluminum glass, the electric field-temperature gradient coupling strengthening technology is adopted, and the electric field is assisted to accelerate: a 75 V / cm DC electric field is applied in a 30% Na⁺ + 70% K mixed salt at 410 °C, and the strengthening time is 3 h.

2. The preparation method of a high-aluminum glass with high strength and high transmittance according to claim 1, characterized in that, The preparation method includes at least the following steps: Step 1: Batching and mixing, weighing raw materials according to the above component ratios, loading them into a mixer and mixing evenly to obtain evenly mixed raw materials; Step 2: Melting, placing the evenly mixed raw materials obtained in Step 1 in a melting furnace for melting to obtain molten glass; Step 3: Forming, forming the molten glass obtained in Step 2 in a press to obtain formed glass; Step 4: Annealing, placing the formed glass obtained in Step 3 in an annealing furnace for annealing treatment to obtain the high-aluminum glass to be strengthened; Step 5: Strengthening, strengthening the high-aluminum glass to be strengthened obtained in Step 4 with a mixed salt to obtain a high-aluminum glass with high strength and high transmittance; Step 6: Performance testing, performing performance testing on the high-aluminum glass with high strength and high transmittance obtained in Step 5.

3. The preparation method according to claim 2, wherein The conditions for melting described in Step 2 are as follows: The melting temperature is 1600 - 1650 °C; The melting time is 3 - 8 h.

4. The preparation method according to claim 2, wherein The conditions for forming described in Step 3 are as follows: The forming temperature is 880 - 950 °C; The forming time is 4 - 6 h.

5. The preparation method according to claim 2, characterized in that The conditions for annealing described in Step 4 are as follows: The annealing temperature is 610 - 645 °C; The annealing time is 2 - 8 h; The transmittance of the glass to be strengthened described in Step 4 at 550 nm is 90 - 95%, and the strain point is 560 - 595 °C.

6. The preparation method according to claim 2, characterized in that, The mixed salt described in Step 5 is selected from at least one of potassium nitrate, potassium carbonate, and potassium chloride; The concentration of the mixed salt is 0.1 - 4 mol / L; The conditions for strengthening described in Step 5 are as follows: The strengthening temperature is 400 - 450 °C; The strengthening time is 1 - 10 h.

7. The preparation method according to claim 2, characterized in that, The surface stress of the high-aluminum glass with high strength and high transmittance described in Step 5 ≥ 1000 MPa, and the depth of the stress layer DOL ≥ 50 μm.

Citation Information

Patent Citations

  • Aluminosilicate glass and preparation method thereof

    CN108706867A

  • Glass for chemical strengthening and chemically strengthened glass

    CN109219583A

  • Method for improving light transmittance of photovoltaic glass by adjusting dielectric constant through alkali metal ion embedding

    CN114956603A

  • Medium aluminum glass as well as preparation method and application thereof

    CN116514391A

  • Composition for preparing high-aluminum glass, high-aluminum glass as well as preparation method and application of high-aluminum glass

    CN116903248A